PENGGUNAAN MEDIA SOSIAL BRANDING PRIBADI SEBAGAI MEDIA PEMBELAJARAN DALAM MENGEMBANGKAN KETERAMPILAN AKADEMIK TERHADAP PEMBELAJARAN INDEPENDEN DI ERA DIGITAL - Nurul Azizah; Wilma Cordelia Izaak (Procuratio : Jurnal Ilmiah Manajemen, 2020)
The existence of social media is increasingly being used by various organizations to attract consumers, especially teenagers. As a form of balance in the use of social media, universities should also optimize its use to improve student academic skills. Higher education institutions are required to be able to carry out an effective learning model. Market changes require higher education institutions to have capability in innovation and responsiveness in making students able to compete so as to create quality graduates. In preparing quality students, it is influenced by the knowledge of independent learning that will be created, resulting in an increase in student activity and personal branding as capable students in the digital era. The purpose of this study was to see how much influence the personal psychology factor (personal five trait) has on the use of social media in creating personal branding and learning models in response to the objectives of independent learning and independent universities. The questionnaire was given to students who were in the university environment using purposive sampling technique and obtained 146 respondents. Reliability and validity are measured through the average variation and Cronbach's alpha analysis. The analysis uses the SEM model structure with SmartPLS which is used to test the relationship between variables. The results of the correlation test obtained scores that are all significant, the highest value on the correlation of learning media to personal branding, meaning that the personal formation of students is strongly influenced by the learning media provided. The lowest hypothesis value is found in the correlation test of learning media to social media usage, meaning that learning media has a relatively low effect on the use of social media by students. Eksistensi social media semakin banyak di gunakan berbagai organisasi untuk menarik para konsumennya, khususnya bagi remaja. Sebagai bentuk keseimbangan pengunaan social media sudah seharusnya perguruan tinggi juga mengoptimalkan penggunaannya untuk meningkatkan skill akademik mahasiswa. Institusi pendidikan tinggi dituntut untuk mampu melakukan model pembelajaran yang efektif. Perubahan pasar menuntut institusi pendidikan tinggi untuk memiliki kepabilitas dalam inovasi dan ketanggapan dalam membuat mahasiswa untuk dapat bersaing sehingga menciptakan lulusan yang berkualitas. Dalam mempersiapkan mahasiswa yang berkualitas dipengaruhi oleh pengetahuan tentang belajar merdeka yang akan diciptakan sehingga menghasilkan peningkatan pada keaktifan mahasiswa dan personal branding sebagai mahasiswa yang mumpuni di era digital. Tujuan penelitian ini adalah untuk melihat seberapa besar pengaruh faktor psyocology personal (personal five trait) terhadap pemanfaatan sosial media dalam menciptakan personal branding dan model pembelajaran dalam merespon tujuan pembelajaran merdeka dan universitas merdeka. Kuesioner diberikan kepada mahasiswa yang berada pada lingkungan universitas dengan menggunakan teknik sampling purposive sampling diperoleh sejumlah 146 responden. Reliabilitas dan validitas diukur melalui rata – rata variasi dan analisis Cronbach’s alpha, Analisis menggunakan struktur model SEM dengan smartPLS yang digunakan untuk menguji hubungan antar variabel. Hasil uji korelasi diperoleh nilai yang seluruhnya signfikan, nilai tertinggi pada korelasi media pembelajaran terhadap personal branding, artinya pada pembentukan personal mahasiswa sangat dipengaruhi oleh media pembelajaran yang diberikan. Nilai hipotesis terendah terdapat pada uji korelasi media pembelajaran terhadap social media usage, artinya media pembelajaran berpengaruh relative rendah terhadap penggunaan social media oleh mahasiswa.